INNOVATIVE MODELS OF EDUCATION AND TRAINING OF SKILLED PERSONNEL FOR HIGH TECH INDUSTRIES IN UKRAINE - Bykov, V.; Shyshkina, M. (Journal of Information Technologies in Education (ITE), 2013)
The problems of development of innovative learning environment of continuous education and training of skilled personnel for high-tech industry are described. Aspects of organization of ICT based learning environment of vocational and technical school on the basis of cloud computing and outsourcing are revealed. The three-stage conceptual model for perspective education and training of workers for high-tech industries is proposed. The model of cloud-based solution for design of learning environment for vocational education and training of skilled workers is introduced.